Using Seawater to Document Coral-Zoothanthella Diversity: A New Approach to Coral Reef Monitoring Using Environmental DNA - Shinzato, Chuya; Zayasu, Yuna; Kanda, Miyuki; Kawamitsu, Mayumi; Satoh, Noriyuki; Yamashita, Hiroshi; Suzuki, Go (Frontiers in Marine Science, 2018)
Frequent, high-density coral monitoring is essential to understand coral reef ecosystems. For this purpose, we developed a novel method for simultaneous monitoring of Acropora corals and their symbiont, Symbiodinium, from environmental DNA (eDNA) in seawater using next generation sequencing technology (NGS). We performed a tank experiment with running seawater using 19 Acropora species. Complete mitochondrial genomes of all the Acropora species were assembled to create a database and major types of their Symbiodinium symbionts were identified. Then eDNA was isolated by filtering inlet and outlet seawater from the tanks. Acropora and Symbiodinium DNA were amplified by PCR and sequenced. We detected all of the tested Acropora types from eDNA samples. Proportions of the DNA sequences and the weights of corals, and the number of DNA sequences and the masses of corals were positively correlated in the tanks, respectively. In this trial, we detected DNA sequences from as little as 0.04 kg of Acropora colony, suggesting that existence of at least one adult Acropora colony (approx. 30 cm diameter = 1kg) per m2 at depths <10m could be detected using eDNA in the field. In addition, we detected major types of Symbiodinium within host corals from seawater, suggesting that it should be possible to detect major coral symbiont types if Acropora corals exist nearby, and possible free-living state Symbiodinium cells from eDNA in sea water. eDNA abundance of Symbiodinium types did not correlate well with frequencies of major Symbiodinium types in the corals, suggesting that quantification of Symbiodinium is difficult at this stage. Although this is the initial attempt to detect coral and Symbiodinium simultaneously from eDNA in seawater, this method may allow us to perform high-frequency, high-density coral reef monitoring of both corals and their symbionts in the near future.